2018
DOI: 10.1007/s12094-018-1844-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and aging in Ibero-America

Abstract: Population aging represents a worldwide challenge. In Ibero-America (Spain, Portugal, and the American countries in which the Spanish or Portuguese language are spoken), the number of older adults is growing, leading to an increase in aging-related diseases such as cancer. Older adults already account for half of all cancer cases in Ibero-America, and this proportion will continue to increase. Furthermore, Ibero-American healthcare systems are not adequately prepared to provide care for older adults with cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
0
24
0
4
Order By: Relevance
“…Data from the National Household Sample Survey (PNAD) of 2008 showed that the prevalence of cancer in the ages between 60 and 69 years, 70 to 79 and 80 years or more, were 1.93%, 3.11% and 3.57%, respectively 9 . In addition to investments in prevention policies and the necessary assistance to cancer patients 3,10,11 , with the aging of the population there is also a demand for the expansion of training for oncogeriatric care 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Data from the National Household Sample Survey (PNAD) of 2008 showed that the prevalence of cancer in the ages between 60 and 69 years, 70 to 79 and 80 years or more, were 1.93%, 3.11% and 3.57%, respectively 9 . In addition to investments in prevention policies and the necessary assistance to cancer patients 3,10,11 , with the aging of the population there is also a demand for the expansion of training for oncogeriatric care 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is experiencing one of the fastest rates of population aging worldwide, and by 2060 approximately a third of all Brazilians will be aged 60 years or older [17]. In contrast, Brazil has few geriatricians, with recent statistics showing that there is one geriatrician for every 15,000 to 22,000 older Brazilians [14,18]. In this context, practical tools such as the CARG chemotherapy toxicity risk calculator (which is also freely accessible online at mycarg.org/tools) may represent valuable assets for clinicians at the point of care, which makes translating and validating them very relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Various initiatives have been implemented to provide geriatric assessment-based care for older patients living in LMIC [12], including the creation of geriatric oncology programs in Brazil and in other Latin American countries [13,14]. However, in order to successfully implement current recommendations in clinical practice, the translation of validated geriatric assessment-based chemotherapy toxicity tools is needed [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these clinics exist within cancer centers in urban areas of developed countries, where resources may be readily available. In contrast, in LMICs, the availability of geriatric oncology clinics is limited …”
mentioning
confidence: 99%
“…In contrast, in LMICs, the availability of geriatric oncology clinics is limited. 7,8 The first multidisciplinary geriatric oncology clinic in Mexico was established in 2015 at Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán (INCMNSZ), a third-level public hospital in Mexico City providing care for uninsured patients. 9 This clinic follows a consultative model, 10 in which adults aged 65 years or older with newly diagnosed/relapsed solid tumors are referred for evaluation before treatment initiation.…”
mentioning
confidence: 99%